(untitled) (Interdisciplinary Studies Journal, 2026)
This article was prepared through a literature review developed within the scope of the stricto sensu postgraduate course, with the objective of providing a critical and updated review of the literature on ADHD, addressing its implications for education and synthesizing intervention strategies that favor the inclusion and learning of children with the disorder in the school environment. Based on the analysis of existing studies and reports, found in academic sources, significant correlations are observed between Attention-Deficit/Hyperactivity Disorder (ADHD) and the most varied difficulties in the learning process and school performance. Research indicates that ADHD constitutes a high risk factor for low academic performance and high school dropout rates.